Physical activity attenuates neuropsychiatric disturbances and caregiver burden in patients with dementia - Christofoletti, Gustavo; Oliani, Merlyn Mércia; Bucken-Gobbi, Lilian Teresa [UNESP]; Gobbi, Sebastião [UNESP]; Beinotti, Fernanda; Stella, Florindo [UNESP] (Universidade de São Paulo (USP), Faculdade de Medicina, 2011)
INTRODUCTION: A significant benefit from physical activity has recently been described in some patients who suffer from neurodegenerative diseases. OBJECTIVE: To assess the effects of physical activity on neuropsychiatric disturbances in demented patients and on the mental burden of their caregivers. METHODS: Assisted by a public geriatric psychiatry clinical unit, we studied 59 patients with dementia. Patients were divided into three groups according to their diagnosis and level of physical activity. Data were assessed through a semi-structured interview. Patients were evaluated with the Neuropsychiatric Inventory, the Mini-Sleep Questionnaire and the Baecke Questionnaire. The data were statistically analyzed using the Mann-Whitney U test and linear regression, with the level of significance set at 5%. RESULTS: Patients with Alzheimer's or vascular dementia who engaged in physical activity had fewer neuropsychiatric symptoms than those who did not. When compared to the control group, the caregivers of patients with vascular dementia who engaged in physical activity had a reduced burden. CONCLUSION: The regular practice of physical activity seems to contribute to a reduction in neuropsychiatric symptoms in dementia patients and to attenuate the burden of the caregivers of those patients.
Keywords: Dementia; public health; exercise therapy; geriatric psychiatry; caregivers